Circulating exosomal microRNA profiles in migraine patients receiving acupuncture treatment: A placebo-controlled clinical trial - Liu, Lu; Qi, Wenchuan; Wang, Yanan; Ni, Xixiu; Gao, Shan; Zhou, Ziyang; Chen, Daohong; He, Zhenxi; Sun, Mingsheng; Wang, Ziwen; Cai, Dingjun; Zhao, Ling (Frontiers in Molecular Neuroscience, 2023)
Background: Acupuncture has a long history of being used in Chinese medicine for the treatment of migraine. However, molecular biomarkers for diagnosis and prognosis of migraine and its treatment are lacking. This study aimed to explore whether acupuncture could regulate differentially expressed exosomal miRNAs between patients with migraine without aura (MWoA) and healthy controls (HCs) and to identify diagnostic biomarkers that helped differentiate MWoA patients from HCs and identify prognostic biomarkers that helped to predict the effect of acupuncture. Methods: Here, we isolated serum exosomes from patients with MWoA and HCs before and after true and sham acupuncture treatment. Then, small RNA sequencing and bioinformatics analysis were performed to screen out key miRNAs specifically responding to acupuncture treatment. Pearson’ s correlation analysis was used to evaluate the correlation between miRNAs and clinical phenotypes. Finally, we applied a machine learning method to identify diagnostic biomarkers of MWoA patients and identify prognostic biomarkers that helped to predict the effect of acupuncture. Results: Small RNA sequencing identified 68 upregulated and 104 downregulated miRNAs in MWoA patients compared to those in HCs. Further, we identified eight upregulated and four downregulated miRNAs in migraine patients after true acupuncture treatment (trAMWoA), but not in the sham acupuncture treatment (shAMWoA) or HC group. Among them, has-miR-378a-5p was positively correlated with time unable to work, study, or do housework due to migraine (p < 0.05), whereas has-miR-605-3p was negatively correlated with the restrictive subscale of the migraine-specific quality of life questionnaire (MSQ) (p < 0.05). We then evaluated the diagnostic and prognostic potential of these 12 miRNAs in patients with MWoA. The combination of serum levels of exosomal has-miR-369-5p, has-miR-4732-5p, and has-miR-550a-3-5p could serve as diagnostic and prognostic biomarkers for MWoA patients following acupuncture treatment. Conclusions: This is the first study on the serum exosomal miRNA profiles of migraineurs before and after acupuncture treatment. Our results improve our understanding of the molecular functions of miRNAs in MWoA. More importantly, they expand our view of evaluating the clinical outcomes of migraine patients treated with acupuncture, using exosomal RNA markers.